Internal Migration Patterns of National and Foreign Population in Italy. A Local Spatial Comparative Approach - Buonomo, Alessio; Gatti, Rosa; Benassi, Federico (Migration Letters, 2023)
A local spatial comparative approach to study internal migration of national and foreign population in Italy is proposed in the paper. Univariate and bivariate local analysis of spatial autocorrelation of internal migration rates of the two populations is conducted. Results are mapped and crossed with municipalities typologies identified by the Degree of Urbanization (Degurba) classification. The local scale of analysis allows to appreciate specific patterns of internal migrations normally ignored. Specifically, a dual spatial regime emerges between geographical patterns of internal migration of nationals and foreigners in terms of urban-rural divide and level of spatial polarization.